Transforming packaging for food products - Klymenko, T.; Bukhalenkova, А. (ТОВ «Друкарня Мадрид», 2024)
Food packaging has a life cycle that is standard for any packaging: "production –use – disposal – recycling". Packaging manufacturers strive to ensure the cyclical use of materials, because it is more profitable to spend resources on conversion than on disposal.
Keywords: food products; packaging